2023
DOI: 10.1093/plphys/kiad346
|View full text |Cite
|
Sign up to set email alerts
|

(Z)-3-Hexenol integrates drought and cold stress signaling by activating abscisic acid glucosylation in tea plants

Abstract: Cold and drought stresses severely limit crop production and can occur simultaneously. Although some transcription factors and hormones have been characterized in plants subjected each stress, the role of metabolites, especially volatiles, in response to cold and drought stress exposure is rarely studied due to lack of suitable models. Here, we established a model for studying the role of volatiles in tea (Camellia sinensis) plants experiencing cold and drought stresses simultaneously. Using this model, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…It has been shown that volatile compounds could ensure the survival of plants under severe cold conditions by maintaining membrane integrity and fluidity through the accelerated synthesis of abundant unsaturated fat [ 38 ]. Studies in several medicinal plants, such as Litsea cubeba , Camellia sinensis , and Astragalus mongholicus , have shown that the levels of their volatile oil are most positively correlated with higher latitude or lower annual average temperature [ 37 , 39 , 40 , 41 ]. The evolution research of the genus Juglans through pan-genome analyses further revealed that in eastern black walnut, with the sharp reduction of the effective population during the glacial climate, there was a large number of InDel sites in the genes involved in fatty acid synthesis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that volatile compounds could ensure the survival of plants under severe cold conditions by maintaining membrane integrity and fluidity through the accelerated synthesis of abundant unsaturated fat [ 38 ]. Studies in several medicinal plants, such as Litsea cubeba , Camellia sinensis , and Astragalus mongholicus , have shown that the levels of their volatile oil are most positively correlated with higher latitude or lower annual average temperature [ 37 , 39 , 40 , 41 ]. The evolution research of the genus Juglans through pan-genome analyses further revealed that in eastern black walnut, with the sharp reduction of the effective population during the glacial climate, there was a large number of InDel sites in the genes involved in fatty acid synthesis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…To knock down csn-miR156f-2-5p expression, 1 mL of 50 μM AsODN-csn-miR156f-2-5p solution was injected into the leaves of hydroponic tea plant seedlings, and seedlings injected with sODN were used as controls. After incubation for 24 h, tea plants were treated with 15% ( w / v ) polyethyleneglycol (PEG) 6000 for 24 h (sODN/AsODN) [ 6 ]. Three independent biological replicates were established for each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…These may be morphological, physiological, or related to water stress sensing, stress signal transduction, and related gene expression regulation [ 5 ]. Recent studies have shown that (Z)-3-hexanol and eugenol can enhance the drought tolerance of tea plants by mediating glucosylation [ 6 ]. An exogenous application of 24-epibrassinolide can improve the drought resistance of tea plants by promoting the expression of genes involved in the biosynthesis of galactinol and abscisic acid [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, other higher-temperature storage may not efficiently prevent the release of ethylene and fruit respiration, which is not conducive to the maintenance of fruit quality. Aroma substances, such as 2-hexenal and (E)-3-hexen-1-ol [33,34], related to non-decay were more abundant at 0-2 • C, which was likely associated with the decrease in ethylene release and fruit energy metabolism during postharvest storage.…”
Section: Effect Of Temperature On Fruit Flavor Qualitymentioning
confidence: 99%